2016
DOI: 10.1161/jaha.115.002667
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure Complicating Acute Myocardial Infarction; Burden and Timing of Occurrence: A Nation‐wide Analysis Including 86 771 Patients From the Cardiovascular Disease in Norway (CVDNOR) Project

Abstract: BackgroundCoronary heart disease (CHD) represents often the underlying conditions for the development of heart failure (HF). We aimed at exploring the burden and timing of HF complicating an acute myocardial infarction (AMI), using the total population of AMI patients hospitalized during 2001–2009 in Norway.Methods and ResultsA total of 86 771 patients with a first AMI during 2001–2009 and without previous HF were identified in the “Cardiovascular Disease in Norway” project and followed until HF development, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 37 publications
1
57
0
7
Order By: Relevance
“…However, previous studies have indicated that the incidence rates of HF were highest during the first 6 months after myocardial infarction, after which they leveled off and remained stable. 28 Besides, the initiation and maladaptive cardiac remodeling seems to be greatest within 30 days after the attack. 29 By comparing patients with and without post-infarct HF, we found that the expression levels of the hub genes were also generally higher with the first 30 days but reached similar at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have indicated that the incidence rates of HF were highest during the first 6 months after myocardial infarction, after which they leveled off and remained stable. 28 Besides, the initiation and maladaptive cardiac remodeling seems to be greatest within 30 days after the attack. 29 By comparing patients with and without post-infarct HF, we found that the expression levels of the hub genes were also generally higher with the first 30 days but reached similar at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of HF during follow‐up was identified using discharge diagnosis codes (ICD‐10 codes, I50.x). HF was classified as “ in‐hospital HF” if diagnosed during the hospital stay for the incident AMI and “ postdischarge HF” if developed within 1 year after discharge from the incident AMI …”
Section: Methodsmentioning
confidence: 99%
“…HF was classified as "in-hospital HF" if diagnosed during the hospital stay for the incident AMI and "postdischarge HF" if developed within 1 year after discharge from the incident AMI. 21 The relative excess mortality associated with HF (also referred to here as the "prognostic impact of HF") was calculated as the ratio between the odds of dying among AMI patients with HF and those without HF. The prognostic impact of in-hospital HF was explored in connection with in-hospital mortality.…”
Section: Study Population Exposure and Outcomesmentioning
confidence: 99%
“…Heart disease, including heart failure, myocardial infarction (MI), and ischemia reperfusion (I/R), is one of the causes of mortality and morbidity worldwide 1, 2, 3, 4. Numerous studies have demonstrated that MI and I/R injuries lead to various types of cardiomyocyte cell death (e.g., necrosis, apoptosis, and autophagy) 5, 6.…”
Section: Introductionmentioning
confidence: 99%